Оптико-спектроскопічні дослідження природних і штучних Cr3+-вмісних клінопіроксенів за високих значень тиску - Таран, М.М.; Охаші, Х.; Лангер, К.; Вишневський, О.А. (Мінералогічний журнал, 2010)
Вивчено поляризовані оптичні спектри поглинання, зумовлені електронними dd-переходами іонів Cr3+ у природному хромдіопсиді, штучно вирощених кристалах космохлору NaCrSi2O6 та його літієвого аналога — LiCrSi2O6-клінопіроксену, а також вплив гідростатичного стиснення на поведінку дозволених і заборонених за спіном смуг і ліній поглинання VICr3+. Оцінено величину модуля об’ємного стиснення структурних CrО6-октаедрів і залежність від тиску параметра Рака В, величина якого відображає ступінь іонності-ковалентності зв’язків Cr—О. Изучены поляризованные оптические спектры поглощения, обусловленные элек трон ными dd-переходами ионов Cr3+ в природном хромдиопсиде и искусственно выращенных кристаллах космохлора NaCrSi2O6 и его литиевого аналога — LiCrSi2O6-клинопироксена, а также влияние гидростатического сжатия на поведение разрешенных и запрещенных за спином полос и линий поглощения VICr3+. Оценена величина модуля объемного сжатия структурных CrО6-октаэдров и зависимость от давления параметра Рака В, величина которого отображает степень ионности-ковалентности связей Cr—О. Comparison of polarized optical absorption spectra of three samples studied, natural Ca-rich diopside and synthetic NaCrSi2O6 and LiCrSi2O6 clinopyroxenes, evidences as vivid similarities, as noticeable differences. The similarities reflect the fact that in all three cases Cr3+ enters the small octahedral M1-site of the clinopyroxene structure. The differences are due to some iron content in the natural sample causing broad intense near infrared bands of electronic spin-allowed ddtransitions of Fe2+(M1, M2) and intervalence Fe2+, Fe3+ charge-transfer transition, and, for the visible range wherein the spectroscopic features caused by Cr3+ predominate, by different symmetry and different local crystal fields strength of Cr3+ in the three crystal structures. The positions of the spin-allowed bands of Cr3+, especially of the low energy one caused by the electronic 4A2g → 2T1g transition, are found to be in accordance with mean M1—O distance in the three pyroxenes. Evaluation of the actual local <Cr—O> distance in the natural diopside studied gives ~2.003 Å. From this the relaxation parameter ε calculated for limCr3+ → 0 from the spectra and interatomic <Cr—O> and <Mg—O> distances yields a very high value 0.96, indicating that in case of a such heterovalent substitution the local lattice relaxation around the "guest" ion, Cr3+, much more deviates from the "diffraction" value, ε = 0, than at isovalent substitutions like Cr3+ → Al3+. Under pressure the spin-allowed bands of Cr3+ shift to higher energies and decrease in intensity, quite in accordance with the crystal field theoretical expectations, while the spin-forbidden absorption lines remain practically un-shifted, being also undergone a strong weakening. There is no evident dependence of the Racah parameter B of Cr3+ reflecting the covalence of the oxygenchromium bond on pressure: within the uncertainty of determination it may be regarded as practically constant. The values of CrO6 octahedral modulus, klocpoly , derived from high-pressure spectra of natural chromium diopside and synthetic NaCrSi2O6 kosmochlore are nearly the same, ~203 and ~196 GPa, respectively, being, however, nearly twice higher than that of MgO6 octahedron in diopside, 105(4) GPa, obtained by Thompson and Downs (2008). Such a strong stiffening of the structural octahedron, i. e. twice higher value of kloc Cr3+ comparing with that of kloc Mg2+, may be caused by simultaneous substitution of Ca2+ by larger Na+ in the neighboring M2 sites at so-called jadeite coupled substitution Mg2+ + + Ca2+ → Cr3+ + Na+. It is also remarkable that the values of CrO6 octahedral modulus of NaCrSi2O6 kosmochlore obtained here are nearly twice larger than that of 90(16) GPa, evaluated by high-pressure X-ray structural refinement by Origlieri et al. (2003). Taking into account that the overall compressibility of the clinopyroxene structure should mainly be due to the compressibility of M1- and M2-sites, our kloc Cr3+ -value, ~196 GPa, looks much more consistent with the bulk modulus value, 134(1) GPa.